Floristic checklist from the hills La Cantera and Delgado, Jantetelco, Morelos, Mexico - Cerros Tlatilpa, Rosa; Ceja-Romero, Jacqueline; Mendoza-Ruiz, Aniceto; Flores-Morales, Alejandro; Jaramillo-Sánchez, Mayo (Instituto de Ecología, A.C., 2020)
Background and Aims: Despite the intense floristic and taxonomic work in Morelos state, there are still some little explored areas. In this study afloristic inventory of vascular plants is presented from the hills Delgado and La Cantera, located at the archeological zone of Chalcatzingo, in the municipality of Jantetelco, Morelos, Mexico.Methods: In order to carry out the work, during the years 2014 to 2017, fieldwork was conducted to collect fertile specimens, which were driedand later identified with specialized keys. The taxonomic identification was verified with herbarium specimens, and in some cases was confirmed byspecialists.Key results: A total of 85 families, 285 genera, 434 species with 27 infraspecific categories of vascular plants were recorded. Eudicots were the mostdiverse group with 66 families, 210 genera and 305 species, followed by monocots with ten families, 57 genera and 100 species, the pteridophyteswith eigth families, 15 genera and 25 species and the magnoliids with three family, three genus and four species. In addition, nine new records arealso reported at a specific level for the state.Conclusions: The study area records 42.7% of the families, 26.6% of the genera and 12.4% of the species registered so far from Morelos, which confirms the cultural and biological importance of this site and highlights the need to continue with the botanical exploration in this part of Morelos.